A retrospective analysis of tuberculosis in livestock farmers in Lahore district, Pakistan - Chanda Jabeen; Muhammad Hassan Mushtaq; Jawaria Ali Khan; Gulshan Umbreen; Muhammad Saqib Saeed; Shakera Sadiq; Rubab Maqsood; Hamad Bin Rashid; Muhammad Asif; Khalid Iqbal; Mamoona Chaudhry (Journal of Infection in Developing Countries)
Introduction: Mycobacterium tuberculosis is the main cause of tuberculosis in humans, accounting for numerous illnesses and thousands of fatalities globally. Data regarding the association of various risk factors and TB in livestock farmers in Pakistan is scarce.